SMART CITY DALAM PERSPEKTIF COLLABORATIVE GOVERNANCE - Novita, Dila; Riskyani, Siska Kartikasari; Nuryono, Rahmat; Muis, Abdul (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2023)
Cities in the world have their own problems such as congestion, flooding, pollution, and urbanization. The DKI Jakarta Provincial Government through the development of a smart city seeks to deal with problems in Jakarta. In implementing a program, the government does not only work alone, but requires multi-stakeholder cooperation. For this reason, this study aims to analyze the implementation of smart cities in Jakarta, analyze collaborative governance in Jakarta Smart City, and analyze public involvement in Jakarta Smart City. This research uses constructivism paradigm with qualitative method and case study design. Data collection techniques through in-depth interviews, observation, and documentation, using purposive sampling and snowball sampling techniques. Data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The results show that the implementation of the Jakarta smart city in 2021 focuses on the pillars of smart living in the health sector due to the Covid-19 pandemic, and smart governance in managing public complaints. Collaborative governance in the implementation of the Jakarta smart city, begins with JSC conducting analysis and research to determine which partners will be invited to collaborate. The collaboration process goes through several stages, a) discussion/dialogue in determining the program, b) building trust and building commitment, carried out through the signing of cooperation, c) mutual understanding is built from the discussions that have been carried out, d) from the collaboration it is expected to provide public services optimal. After that, the community participated in the development of smart cities through community aspirations through e-musrenbang, actively reported problems they experienced in society and helped promote JAKI, had easy access to public services, and evaluated through surveys and in-depth interviews with the public.